ACTIVE LEARNING TECHNIQUES FOR DEVELOPING CRITICAL THINKING SKILLS - Muratova Nargiza Bakhramovna (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
The development of critical thinking skills is a fundamental objective in contemporary education. This article examines the effectiveness of active learning techniques in fostering critical thinking among students. Active learning methods — including think-pair-share, case studies, structured debates, problem-based learning, and Socratic seminars — require students to engage analytically, reflectively, and collaboratively with complex material. The article outlines how these strategies promote higher-order cognitive skills such as inquiry, analysis, evaluation, and synthesis. Additionally, it discusses practical considerations for implementing active learning approaches, including the importance of setting clear objectives, creating an inclusive and supportive learning environment, and providing timely, constructive feedback. The findings suggest that incorporating active learning strategies significantly enhances students' critical thinking abilities, preparing them for complex problem-solving and independent thought in academic and professional contexts.